2020
DOI: 10.1002/celc.202000769
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited Tin‐Antimony Alloys as Novel Electrocatalysts for Selective and Stable Carbon Dioxide Reduction to Formate

Abstract: The activity of SnSb alloy films as electrocatalysts for the CO 2 reduction reaction (CO 2 RR) to formate was presented for the first time. The effects of the film composition, electrochemical potential, and nature and concentration of the supporting electrolyte on the activity and long-term stability of these catalysts were evaluated. Sn 9 Sb 1 alloy exhibited improved longterm stability when compared to pure Sn films, and this was attributed to the lower insertion of alkali and lower formation of hydride spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…For instance, He and co-workers published a detailed review about bimetallic mixtures and the studies showed an improvement in the performance for the CO 2 reduction due to the use of these systems. [19] More recently, works have continued this topic using SnÀ PbÀ Sb alloy foil, [20,21] nanoporous CuÀ Ag alloys, [22] CuÀ Sn alloys, [23][24][25][26] SnÀ Sb alloys, [27] CuÀ Sb alloys, [28] CuÀ Bi amorphous bimetallic electrocatalysts, [29] or InÀ Sn alloy core-shell nanoparticles. [30] Tin and bismuth are the most studied metals for the CO 2 RR towards formic acid/formate and, with respect to them, recent bimetallic studies have revealed that the Bi presence improves the performance of Sn catalysts, [31,32] although pure Bi catalysts outperform those combining Sn and Bi.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, He and co-workers published a detailed review about bimetallic mixtures and the studies showed an improvement in the performance for the CO 2 reduction due to the use of these systems. [19] More recently, works have continued this topic using SnÀ PbÀ Sb alloy foil, [20,21] nanoporous CuÀ Ag alloys, [22] CuÀ Sn alloys, [23][24][25][26] SnÀ Sb alloys, [27] CuÀ Sb alloys, [28] CuÀ Bi amorphous bimetallic electrocatalysts, [29] or InÀ Sn alloy core-shell nanoparticles. [30] Tin and bismuth are the most studied metals for the CO 2 RR towards formic acid/formate and, with respect to them, recent bimetallic studies have revealed that the Bi presence improves the performance of Sn catalysts, [31,32] although pure Bi catalysts outperform those combining Sn and Bi.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above-mentioned issues, another type of poisoning phenomenon was observed in a study by Hori et al [60], where a deterioration in catalyst activity was associated with the deposition of metal impurities from the electrolyte onto the catalyst surface to form a new layer that both blocks the original active sites and provides activity towards the hydrogen evolution reaction [53,55,61]. This finding was supported by later studies that indicated the deposition of metal impurities, which may be present even in trace amounts in the electrolyte, the water source, the electrocatalyst, or the support materials [62].…”
Section: Catalyst Poisoningmentioning
confidence: 99%
“…In terms of catalyst design, modulating the electronic structure provides the benefits of directly adjusting the binding energies of the reaction intermediates. Thus, Zhang et al [100] described several strategies for modifying the electronic structure, including the use of alloying [87,101], single-atom catalysts [102], phase-junction catalysts [61], and surface groups [69]. Among these strategies, the alloying of several metals are particularly promising for relieving the poisoning of the catalyst by intermediates.…”
Section: Modifying the Electronic Structurementioning
confidence: 99%
See 2 more Smart Citations